2020
DOI: 10.1021/acssynbio.0c00151
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-dCas9 Mediated Cytosine Deaminase Base Editing in Bacillus subtilis

Abstract: Base editing technology based on Clustered regularly interspaced short palindromic repeats/associated protein 9 (CRISPR/Cas9) is a recent addition to the family of CRISPR technologies. Compared with the traditional CRISPR/Cas9 technology, it does not rely on DNA double strand break and homologous recombination, and can realize gene inactivation and point mutation more quickly and simply. Herein, we first developed a base editing method for genome editing in Bacillus subtilis utilizing CRISPR/dCas9 (a fully nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 45 publications
3
46
0
Order By: Relevance
“…Due to the diverse genome environments in diverse cells and host-dependent factors of some tools, one tool is usually applied for one kind of cell. In addition, the tools also displayed significantly different conversion efficiency even in one kind of cell because of the different expression version and construction strategy ( 31 , 32 ). No matter how to use these tools, a BE with high stability and high conversion efficiency is expected.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the diverse genome environments in diverse cells and host-dependent factors of some tools, one tool is usually applied for one kind of cell. In addition, the tools also displayed significantly different conversion efficiency even in one kind of cell because of the different expression version and construction strategy ( 31 , 32 ). No matter how to use these tools, a BE with high stability and high conversion efficiency is expected.…”
Section: Introductionmentioning
confidence: 99%
“…Since the development of CBE system in eukaryotes (Komor et al, 2016), base editors have been gradually applied to prokaryotes such as E. coli (Banno et al, 2018), P. aeruginosa (Chen et al, 2018), S. aureus (Gu et al, 2018), Streptomyces (Tong et al, 2019), Corynebacterium glutamicum (Wang et al, 2018), and B. subtilis (Yu et al, 2020). While the eukaryotic CBE system contains nCas9, we used dCas9 as previously reported (Banno et al, 2018;Yu et al, 2020) because we found that nCas9 affects transformation efficiency in B. subtilis (Supplementary Figure S1A). For base editing, cytidine deaminases, rAPOBEC1, and PmCDA1 have been widely used as the component of CBEs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the use of PmCDA1-mediated base editing has been reported in B. subtilis (Yu et al, 2020). The system showed high editing efficiency at position 18 from PAM alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This system can avoid the dependence on HDR and reduce the fatality rate caused by DSBs, but it requires the participation of cytosine deaminase. 38 After checking the nucleotide sequences of T399 and H448, we found that it is not feasible to introduce the desired mutations by base editing events ( Figure 3 B). Therefore, to introduce our desired mutations into GFPADS, it is necessary to create the DSBs by SpCas9 near T399 and H448 and introduce editing templates containing inconsistent sequences with N20 nucleotides.…”
Section: Discussionmentioning
confidence: 99%